Addressing the human rights impacts of economic globalisation: An analysis from soft law and Islamic perspectives - Ahmad, Nisar Mohammad; Ahamat, Haniff; Hassan, Halyani; Mohd Subr, Irwan; Mokhtar, Ahmad Wifaq (2014)
The recent trend of economic globalisation has resulted in massive emergence of international business corporations such as the multinational corporations (MNCs).The inherent aim of their establishment which was based mainly on profit-making has, to a certain extent, put social and human rights interests of their stakeholders at stake.The adverse human rights violations committed by MNCs worldwide, despite responded with mounting protests and concerns by global communities, are not readily addressed. Among the rights mostly affected by business operations include civil and political as well as economic, social and cultural rights.Aiming to enhance human rights compliance by business entities and thus to address the human rights impacts of economic globalisation, this paper seeks to analyse the solution mechanism from the perspectives of soft law approach and Islamic principles.This paper uses the library-based research method by analysing relevant materials such as the UN documents, legal journals, court cases and judgments, academic textual materials as well as internet sources.This paper concludes that there is no divergence between the tenets of Islam and the adoption of corporate responsibility through soft law approaches.Both soft law and Islamic principles could formulate viable solutions to address the mounting events of corporate human rights violations that feature the current era of economic globalisation. This paper believes that a success in harmonising economic growth and protecting human rights principles will harness the great power of economic development to align with the great principle of human dignity.